Magnitude of Domestic Violence Among Married Women of Reproductive Age (15-49) in Ratnanagar Municipality-13, Chitwan - Bhatta, Pramila; Poudel, Kamal; Khanal, Asmita; Shah, Rajani (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Background: Domestic Violence is any form of physical, mental, sexual and economic harm perpetrated by person to a person with whom he/she has a family relationship and this word also includes any acts of reprimand or emotional harm. Methodology: A Discriptive cross-sectional study was conducted among 250 married women of reproductive age of Ratnagear municipality-13, Data was entered and analyzed using SPSS 20, focusing on frequency and percentage. Result: This study identifies the overall prevalence of domestic violence was found to be 14.89%. Where emotional violence was experienced by 21.68% respondents, physical violence was experienced by 15.55% respondents, and sexual violence was experience by 7.46% respondents. Conclusion: In this study among different forms of violence emotional violence was the most common forms of domestic violence, Slapping, beating, twisting arm, pulling hair, kicking were the commonest forms of physical violence, whereas said something bad, being unfaithful, insulting were the common forms of emotional violence and forced to have sexual intercourse were the common form of sexual violence in my study. Keywords: Domestic Violence, Reproductive age, Married Women, Ratnanager Municipality